(untitled) (Research, Society and Development, 2023)
Introduction: Physical training performed on a regular basis seeks to minimize the appearance of pathologies, maintenance of the organic system and improvement in quality of life, which can be acquired through flexibility gain, increased muscle strength and greater body resistance. There are still people who, in addition to performing physical training to achieve these benefits also use it is a formo f work and/ or competition, the so-called athletes. Currently, research is studying whether, in addition to professional training monitoring and healthy eating, the human DNA genetics can have an influence on the athlete’s physical fitness, making it possible for him to have a better physical performance in his sport, reducing the risk of injuries. Objective: To carry out a literature review of scientific findings in the literature seeking the relationship of human genetics with stretching and muscle strength, in addition to expanding the knowledge of professionals pointing out the best ways to achieve good results and minimize the risk of injury. Methods: This is a bibliographic research study in Scielo, Pubmed PEDro, Science databases regarding the relationship of genetics with stretching and muscle strength. Results: 137 articles were selected, where 21 studies were included in the review, ensuring that genetics is related to stretching and muscle strength. Conclusion: Human genetics has an influence on the individual’s physical characteristics, thus contributing to the work of physical training, seeking better results, in addition to minimizing the risk of injuries.